Downstream porosity for the reduction of turbulence–aerofoil interaction noise. (22nd December 2022) - Palleja-Cabre, Sergi; Chaitanya, Paruchuri; Joseph, Phillip; Kim, Jae Wook; Priddin, Matthew J.; Ayton, Lorna J.; Geyer, Thomas F.; Chong, Tze Pei
Abstract: This paper is a predominantly experimental study into the use of porosity located downstream of an aerofoil leading edge for the reduction of turbulence interaction noise. Locating the porosity downstream of the leading edge has been shown to be beneficial in reducing the aerodynamic performance penalty compared with locating it directly at the leading edge (Ocker et al., 2021), where most of the lift is generated. Noise measurements on a flat plate with downstream porosity are compared against the case of two flat plates in a tandem configuration. In both cases, the noise reduction spectra exhibit peaks of strong noise reduction at non-dimensional frequencies of f l d / U c = n, where l d is the distance between the leading edge and the downstream edge, U c is the convection velocity and n is an integer. To explain this behaviour requires a mechanism to be present in which a phase shift of 180 ∘ is introduced in the interaction process. In the paper we argue that the origin of this phase shift is due to secondary vorticity generated at the leading edge. Another key finding of this paper is that overall noise reductions are due to an effective shortening of the chord in which most of the radiation is produced by the section of the flat plate upstream of the porous section, leading to generally weaker radiation. Neither of these mechanisms have been reported previously in the literature. The paper concludes with noise measurements on a thin aerofoil with downstream porosity included, in which overall noise reductions of up to 2.8 dB are achieved. Highlights: Downstream porosity shows similar behaviour to two flat plates in a tandem configuration. Up to 2.8 dB reductions in overall noise are observed on realistic aerofoil geometries. Edge-to-edge interference is present with 180deg phase inversion between the edges. The envelope of noise reductions is releted to an effective shorter chord.